Correlation analysis of monocyte chemoattractant protein-1 and clinical characteristics and cognitive impairment in type 2 diabetes mellitus comorbid major depressive disorder - Cao, Fang; Yang, Mei; Cheng, Yuqi; Zhang, Xiuyue; Shi, Li; Li, Na (Frontiers in Aging Neuroscience, 2023)
Introduction Type 2 diabetes mellitus (T2DM) and major depressive disorder (MDD) are both chronic diseases, and they are often co-morbid. Usually, T2DM and MDD are associated with cognitive impairment, and the comorbidity status of both may increase the risk of cognitive impairment, but the underlying pathogenesis is not clear. Studies have shown that inflammation, especially monocyte chemoattractant protein-1 (MCP-1), could be associated with the pathogenesis of type 2 diabetes mellitus comorbid major depressive disorder. Aims To investigate the correlations of MCP-1 with clinical characteristics and cognitive impairment in type 2 diabetes mellitus patients combined with major depressive disorder. Methods A total of 84 participants were recruited in this study, including 24 healthy controls (HC), 21 T2DM patients, 23 MDD patients, and 16 T2DM combined with MDD (TD) patients, to measure the serum MCP-1 levels using Enzyme-linked Immunosorbent Assay (ELISA). And the cognitive function, depression, and anxiety degree were assessed using Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), 17-item Hamilton Depression Scale (HAMD-17), and Hamilton Anxiety Scale (HAMA), respectively. Results (1) Serum MCP-1 expression levels in the TD group were higher than HC, T2DM, and MDD groups, respectively (p < 0.05). And compared with HC and MDD groups, serum MCP-1 levels in the T2DM group were higher (p < 0.05) statistically. Receiver Operating Characteristic (ROC) curve showed that MCP-1 could diagnose T2DM at cut-off values of 503.8 pg./mL (sensitivity 80.95%, specificity 79.17%, AUC = 0.7956) and of 718.1 pg./mL for TD (sensitivity 81.25%, specificity 91.67%, AUC = 0.9271). (2) Group differences in cognitive function were significant. Compared with the HC group, total RBANS scores, attention scores, and language scores in the TD group were lower, respectively (p < 0.05), and total RBANS scores, attention scores, and visuospatial/constructional scores in the MDD group were lower, respectively (p < 0.05). Compared with the T2DM group, immediate memory scores in HC, MDD, and TD groups were lower, respectively, and total RBANS scores in TD were lower (p < 0.05). (3) Correlation analysis showed that hip circumference was negatively correlated with MCP-1 levels in the T2DM group (R = −0.483, p = 0.027), but the correlation disappeared after adjusting age and gender (r = −0.372; p = 0.117), and there were no significant correlations between MCP-1 and other variables. Conclusion MCP-1 may be involved in the pathophysiology of type 2 diabetes mellitus patients combined with major depressive disorder. And MCP-1 may be significant for the early evaluation and diagnosis of TD in the future.